Pemetaan Muka Air Tanah Berbasis Sistem Informasi Geografis (SIG) sebagai Dasar Mitigasi Kekeringan di Desa Sumberpinang, Kabupaten Jember - Muhammad Iqbal Santoso; Ahmad Zidan Zaki Gunawan; Rehagel Yogo Prastowo; Joel Maruba Manurung; Fikri Lego Utomo; Effel Edelweis (Yayasan Sagita Akademia Maju, 2026)
This study aims to map groundwater levels in Sumberpinang Village, Jember Regency as a basis for drought mitigation using Geographic Information System (GIS) technology. This study applies groundwater depth measurements from community wells which are subsequently analyzed spatially using GIS software. This analysis produces groundwater contour maps, groundwater flow directions, and zones potentially vulnerable to drought. The results show groundwater depth variations ranging from 0.53 m to 4.65 m with groundwater elevation distribution between 146.87 m and 183.82 m above sea level. These variations indicate heterogeneous aquifer characteristics that influence groundwater availability across different locations. The TIRTANALA team conducts community service activities by providing education regarding groundwater conditions and drought mitigation to residents of Sumberpinang Village targeting 200 households. The implementation team also distributes 8 thematic maps in printed form and 50 TIRTANALA pocket books as educational media for the community. The development of the TIRTANALA WebGIS platform also provides an interactive spatial information system displaying groundwater contours, groundwater flow directions, river networks, administrative boundaries, monitoring wells, and drought vulnerability zones. These activities improve community understanding of groundwater conditions and encourage the utilization of spatial data as a basis for water conservation planning and drought mitigation at the village level.